Semiotics of rape : sexual subjectivity and violation in rural India - Oza, Rupal (Duke University Press, 2023)
"In Semiotics of Rape, Rupal Oza follows the social life of rape in rural northwest India to reveal how rape is not only a violation of the body, but a language through which a range of issues-including caste and gender hierarchies, control over land and labor, and the shape of justice-are contested. Rather than focus on the laws governing rape, Oza closely examines rape charges to show how the victims and survivors of rape reclaim their autonomy by refusing to see themselves as defined entirely by the act of violation. Oza also shows how rape cases become arenas where bureaucrats, village council members, caste communities, and the police debate women's sexual subjectivities and how those varied understandings impact the status and reputations of individuals and groups. In this way, rape gains meaning beyond the level of the survivor and victim to create a social category. By tracing the shifting meanings of sexual violence and justice, Oza offers insights into the social significance of rape in India and beyond."--